Hepatitis C reactivation in patients with chronic infection with genotypes 1b and 2c: a retrospective cohort study of 206 untreated patients. Issue 3 (11th February 2005) - Rumi, M G; De Filippi, F; La Vecchia, C; Donato, M F; Gallus, S; Del Ninno, E; Colombo, M
Abstract : Background: We previously described hepatitis reactivation in two carriers of the hepatitis C virus (HCV) genotype 2c. Aim: To assess the relationship between HCV genotypes and risk of hepatitis reactivation, we studied the course of aminotransferases in patients infected with the two relevant genotypes in Italy. Patients: A cohort of 100 patients with genotype 2c chronic hepatitis and 106 with genotype 1b were subjected to surveillance. Methods: Hepatitis reactivation was defined as an alanine aminotransferase (ALT) value ⩾400 IU/l or a maximum/minimum ALT ratio value of ⩾8. Results: Over a period of 71 (24–144) months, one or more flares of ALT (201–2200 IU/l, 6–90 months' duration) occurred in 31 patients with genotype 2c and in eight patients with genotype 1b (rates of flares: 55.6 per 1000 person years for genotype 2c v 15.0 for genotype 1b; p = 0.001). On repeat biopsy, hepatic fibrosis increased by more than 2 points in 10/16 patients examined either during or after an ALT flare compared with 7/36 flare free patients (63% v 19%; p = 0.003). Hepatitis flares were significantly associated with genotype 2c (odds ratio 6.48 (95% confidence interval 2.57–16.35)) but not with sex, age, modality or duration of infection, baseline ALT values or histological severity of hepatitis, hepatitis other than HCV, or reinfection. Conclusions: Genotype 2c carriers are at high risk of hepatitis reactivation, suggesting that virus genetic heterogeneity is important in the natural history of HCV, questioning the linearity of hepatic fibrosis progression during hepatitis C.